Using Coronary Artery Calcium Score as Diagnostic Tool in Symptomatic Chronic Coronary Syndrome Patients in a Real-Life Setting - Witvliet MP; Arkenbout EK; Kamphuisen PW (Vascular Health and Risk Management, 2023)
M Patrick Witvliet,1,2 E Karin Arkenbout,3 Pieter W Kamphuisen1,4 1Department of Internal Medicine, Tergooi Medical Center, Hilversum, the Netherlands; 2Department of General Practice, Amsterdam UMC Location University of Amsterdam, Amsterdam, the Netherlands; 3Department of Cardiology, Tergooi Medical Center, Hilversum, the Netherlands; 4Department of Vascular Medicine, Amsterdam UMC location University of Amsterdam, Amsterdam, the NetherlandsCorrespondence: M Patrick Witvliet, Department of Internal Medicine, Tergooi Medical Center, Laan van Tergooi 2, 1212 VG, Hilversum, the Netherlands, Tel +31 205664271, Email m.p.witvliet@amsterdamumc.nlBackground: The coronary artery calcium (CAC) score can be used to increase (CAC score > 0) or decrease (CAC score = 0) the likelihood of coronary artery disease (CAD). We compared the CAC score with the pre-test probability (PTP) for CAD (low, intermediate, and high). Furthermore, we compared the CAC score with exercise electrocardiography (ECG) and compared both tests with coronary angiography.Methods and Results: We retrospectively identified patients with angina and/or dyspnea for whom CAC score was used to increase or decrease the likelihood of CAD. Of 882 patients, majority had low (45%) or intermediate (44%) PTP. Patients with higher PTP had significantly higher CAC scores (Cramer’s V = 0.29, p < 0.0001). Most patients (57%) had a CAC score of zero, especially those with low (73%) and intermediate (49%) PTP. However, 20% of patients with high PTP had CAC score of zero. Higher CAC scores were observed in patients with abnormal exercise ECG, but association was weak and not significant (Cramer’s V = 0.13, p = 0.08). Moreover, more than 40% of patients with an abnormal exercise ECG had CAC score of zero. Higher CAC scores were associated with more severe abnormalities on coronary angiography (Cramer’s V = 0.43, p < 0.0001), whereas there was no association between results of exercise ECG and coronary angiography (Cramer’s V = 0.11, p = 0.91).Conclusion: CAC score can be used in addition to PTP to increase or decrease the likelihood of CAD, and it might be more useful than exercise ECG in the diagnostic work-up of chest pain.Keywords: coronary artery disease, cardiovascular disease, CT, risk factors, angina, stable